Marriage in Heaven, Marriage on Earth: John Colet and a Difficult Sacrament - Fallica, Maria (Erasmus studies, 2025)
This essay is an analysis of John Colet’s thought about marriage in his manuscript treatise De sacramentis. Colet’s assessment of marriage was famously very harsh, condemning it as a reproachable concession for the weak. The essay argues that this condemnation should be read in the light of the complex protological setting elaborated in the treatise, which shows relevant Patristic models. The essay proposes a comparison with Erasmus, arguing that the difference between the two thinkers on this point lies in a different, broader understanding of the metaphoric level, ecclesiology, and reform.